2022
DOI: 10.1007/s40820-022-00929-y
|View full text |Cite
|
Sign up to set email alerts
|

Al2O3/HfO2 Nanolaminate Dielectric Boosting IGZO-Based Flexible Thin-Film Transistors

Abstract: Highlights A stable laminated Al 2 O 3 /HfO 2 insulator is developed by atomic layer deposition at a relatively lower temperature of 150 °C. The flexible thin-film transistors (TFTs) with bottom-gate top-contacted configuration are fabricated on a flexible substrate with the Al 2 O 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In this regard, thin film transistors (TFT) with active channel material of InGaZnO (IGZO) are considered especially promising [76,77]. It has been shown that HfO 2 /Al 2 O 3 stacks can boost the performance of IGZO-based TFTs [78]. Integration of HfO 2 /Al 2 O 3 stacks in recently reported synaptic transistors based on IGZO nanofibers [79,80] could be a feasible way to enhance their retention characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, thin film transistors (TFT) with active channel material of InGaZnO (IGZO) are considered especially promising [76,77]. It has been shown that HfO 2 /Al 2 O 3 stacks can boost the performance of IGZO-based TFTs [78]. Integration of HfO 2 /Al 2 O 3 stacks in recently reported synaptic transistors based on IGZO nanofibers [79,80] could be a feasible way to enhance their retention characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…[105] The utilization of AOSs as active channel materials in TFTs has gained significant attention in recent years and demonstrated remarkable advances in terms of high μ, low offcurrent, low process temperature, versatile composition, and refined processing flexibility. Various AOSs have been extensively investigated, including In 2 O 3 , [106] Ga 2 O 3 , [107] ZnO, [108] ITO, [109] IGZO, [110] and HfInZnO, [111] with resulting publications available in the academic literature.…”
Section: Amorphous Oxide Semiconductor Tftsmentioning
confidence: 99%
“…For example, InO x can be implemented as an active layer or transparent electrode in thin film transistors, and semiconductor InO x films can be obtained at relatively low temperatures with sufficiently low carrier concentrations. [32][33][34] Therefore, In 2 O 3 is one potential candidate active layer material in thin film transistor devices because its high mobility n-type characteristic comes from the single free electron-like band in the In5s state. The [1,1,1-trimethyl-N-(trimethylsilyl) silanaminato]-indium (InCA-1) as an indium source, H 2 O 2 as an oxidant, and N 2 gas (99.9999%) as the precursor carrier and also to purge the chamber after each reaction.…”
Section: Ald In High-k Gate Dielectricsmentioning
confidence: 99%